PENGEMBANGAN MEDIA PEMBELAJARAN UNTUK PENGENALAN DOUYOU TENTANG MUSIM DI JEPANG PADA SISWA SMA KATOLIK UNTUNG SUROPATI KRIAN - PAKERTI, YONATAN (HIKARI, 2020)
Abstract The rapid development of technology is an opportunity for the usage of computer technology in the learning process. One of computer technology is the Powerpoint program that is increasingly used in the learning process especially the introduction of Japanese, which so far is still only focused on Japanese grammar, such as letters, words, phrases and sentences. Besides that, literature can be taught together with grammar simultaneously, for example childrens songs (Douyou). There are various themes for childrens songs, such as about seasons, celebrations and daily life. Season is very much related to Japanese peoples life. Therefore, in this study, researcher developed Powerpoint media about the season and used this media to research about introducing Japanese culture as well. In this study, 12 season-themed songs will be used. Here is a list of 12 songs, Spring: S?shunbu, haruyokoi, doko ka de haru ga. Summer: Ware ha uminoko, natsuhakinu, natsu no omoide. Autumn: K?y?, ch?sai akits mitsuketa, sato no aki. Winter: Yuki, yuki no furumachiwo, pechika. The purpose of this research is to find out and then describe the development process and test results on Powerpoint learning media to introduce Douyou about seasons in Japan. This research uses The Research & Development method by Sugiyono (2015: 409). In collecting student response we visit Untung Suropati Catholic High School Krian and helped by 20 students as subjects. There are two tests were conducted, the validation by experts and trials to the subjects. based on the validation calculation that is equal to 94.44% by material experts and 90% by media experts, and gets very good student responses with a percentage of 89.58%. Thus the results of this study produce Powerpoint learning media that are suitable for the introduction of Douyou about seasons in Japan.?? ??????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????12??????????????????????????12?????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????SMA Katolik Untung Suropati????????????????????????????20??????????????????????????????????????????????2?????????????????????????????????????????????????????????????90%????????????????94,44%?????????????????89,58%???????????????????????????????????????????????????????????????